Managing environmental dependency syndrome in a person with an acquired brain injury: a simple strategy evaluated using an ABABA design (Gestión del síndrome de dependencia ambiental en un paciente con daño cerebral adquirido: una estrategia simple evaluada mediante un diseño ABABA). Issue 1 (2nd January 2022) - Wilson, Barbara A; Rose, Anita; Fish, Jessica
ABSTRACT: This paper begins with a discussion about environmental dependency syndrome (EDS) and utilization behaviour (UB). Are there differences between the two or are they synonymous terms? Following a description of the two conditions, the case of KI, a 57-year-old man, with both UB and EDS is presented. An easy and inexpensive treatment strategy to reduce his inappropriate responses and increase his attention to rehabilitation is described, and data are provided in the form of an ABABA design to demonstrate the effectiveness of this treatment. The simple therapeutic strategy is advocated for people who use objects in the environment inappropriately.